Analysis of propagation characteristics of UAV communication scenarios based on parabolic equation - Hui HAN; Yulong HAO; Cheng YANG; Jian WANG (Dianxin kexue)
To improve the analysis accuracy of the propagation characteristics of UAV millimeter-wave communication scenarios, a method based on the parabolic equation was developed to analyze the propagation characteristics of UAV communication scenarios and simulate the propagation characteristics in urban and suburban areas.The results show that the proposed method can effectively express the influence of terrain parameters on the UAV air-ground communication link.Overall, the prediction results are consistent with the ITU-R statistical method in both scenarios.Effective prediction of the propagation characteristics of millimeter-wave UAV application scenarios can be realized with the proposed method, which may support the design, development, and testing of UAV millimeter-wave communication systems.